Waqāʾiʿ-i Šāh Muʿīn-ad-Dīn Čištī : sawāniḥ-i ʿumrī wa ḏikr-i karāmāt-i Ḫāǧa-i Ḫāǧagān Muʿīn-al-Ḥaqq Ḥasan Sanǧarī ṯumm al-Aǧmīrī - Bābū Lāl (Nawal Kišūr, 1913)
Stories from the life of Shaikh Muʿīn-ad-Dīn Čištī, founder of the Čištī order